Covid-19 and its effect on trip mode and destination decisions of transit riders: Experience from Ohio. (September 2021) - Simons, Robert A.; Henning, Mark; Poeske, Abigail; Trier, Malcolm; Conrad, Kirt
Highlights: Among transit riders, shopping and work trips dropped 11–19% while social visits and worship trips dropped 49–61% during COVID. Bus, personal car use and paratransit decreased least among all modes of transit during COVID. Being female, married, parents, and having higher income saw largest decreases in trips among transit riders during COVID. Transit riders likelier to fear catching COVID were female, nonwhite, parents, and older. Abstract: This research addresses travel patterns including trip mode and destination before and during the SARS-CoV-2 (COVID-19) pandemic. The team collected surveys from 1081 transit riders in Ohio. Shopping and work trips dropped the least (11–19%) while social visits and worship trips were reduced the most (49–61%). Bus, personal car use and paratransit dropped the least, while walking and ride share dropped the most. Regression analysis revealed that female, married, children at home, higher income, and areas with high COVID infection rates had the largest decreases in trips. Being unbanked and being employed (including while working from home) saw stable or increased trips. Females and those with children felt less connected to the community, but unbanked people did not. Respondents likelier to fear catching COVID were female, nonwhite, have kids, older, and with highest incomes, but being employed or having a driver's license was not associated with increased fear.